Are Outcomes of Non-Invasive Ventilation in Acute Respiratory Failure Similar in Very Old Adults? - Costa,Ana Rita (2020)
Introduction: Acute respiratory failure (ARF) is one of the most prevalent causes of observation in the emergency department in an ageing population. Non-invasive positive pressure ventilation (NIPPV) has shown good results in critically ill with ARF. The evidence of NIPPV outcomes in old patients is scarce. The aim of our study is to analyse outcomes of NIPPV use in this population. Methods: We conducted a prospective observational study in a 12-bed intermediate care unit of an university hospital. We included and consecutively compared patients aged 75 years old or more (study group) and under 65 years old (control group) submitted to NIPPV due to ARF. The primary end point was mortality (in-hospital and 30 daysafter discharge). Secondary endpoints were NIPPV settings, complications, and failure rate. Results: A total of 109 patients were included. In-hospital mortality was significantly higher in the study group (22.2 % vs 8.1%, p< 0.01). However, mortality 30 days after discharge was not significantly different (4.1% vs 4.9%, p = 0.37). NIPPV duration of use (6.1 vs 2.2 days, p < 0.01) and hospital length of stay (14.3 vs 6.2 days, p = 0.01) were higher in the study group. NIPPV failure (22.2% vs 16.1 %, p = 0.09) and complication rate (intolerance 8% vs 6%, p = 0.31; ulcers 4% vs 3%, p = 0.28) were similar in both groups. Conclusion: ARF carries a grim prognosis in older adults. A high mortality rate was observed in older patients despite similar severity assessments and NIPPV failure and complication rates. Notably, out of the hospital mortality is comparable between both groups.